2019
DOI: 10.1038/s41598-019-55654-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the activation and inhibition of Sirtuin 6 by quercetin and its derivatives

Abstract: Mammalian Sirtuin 6 (Sirt6) is an NAD+-dependent protein deacylase regulating metabolism and chromatin homeostasis. Sirt6 activation protects against metabolic and aging-related diseases, and Sirt6 inhibition is considered a cancer therapy. Available Sirt6 modulators show insufficient potency and specificity, and even partially contradictory Sirt6 effects were reported for the plant flavone quercetin. To understand Sirt6 modulation by quercetin-based compounds, we analysed their binding and activity effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 51 publications
1
85
0
Order By: Relevance
“…A subsequent Xray crystal structure of SIRT6 bound with cyanidin confirmed this binding orientation (Fig. 6) (149). Interestingly, treatment of Caco-2 cells with cyanidin showed a dose-dependent increase (3.5-fold) in SIRT6 protein levels (115).…”
Section: Activationmentioning
confidence: 62%
“…A subsequent Xray crystal structure of SIRT6 bound with cyanidin confirmed this binding orientation (Fig. 6) (149). Interestingly, treatment of Caco-2 cells with cyanidin showed a dose-dependent increase (3.5-fold) in SIRT6 protein levels (115).…”
Section: Activationmentioning
confidence: 62%
“…Interestingly, from Figure 4, we can conclude that the two conformationally similar inhibitors have the same binding mode with SIRT6. In the experiments, You et al [23,25] and Lu et al [43] reported the binding sites of potential inhibitors to SIRT6 (Phe64, Phe82 and Phe86 at N terminus). Our results agree well with the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Several amino acid residues (e.g., Ile 61, Pro62, Phe64/82/86, Val70, Asn114, Val115, and Asp116) form a hydrophobic pocket to anchor the molecules in the pocket with polar contact and potential H‐bonds. Most modulators binding in the active site have partial overlap with the pocket where NAM moiety of NAD + occupies (Figure 1A, C site), and thus no ADPr competition but statistically significant NAD + or NAM competition with them are detected in the activity assays 54,296–300 . Importantly, SIRT6 activators binding in this pocket primarily exerts concentration‐dependent deacetylation activity.…”
Section: Sirt6 Modulatorsmentioning
confidence: 99%
“…Importantly, SIRT6 activators binding in this pocket primarily exerts concentration‐dependent deacetylation activity. Some of them has no improvement to or even inhibits the SIRT6‐dependent demyristoylation activity, likely due to the compatible binding of activators with that of acetylated substrates and overlapping with longer acylated substrate 34,35,296,296,300,301 …”
Section: Sirt6 Modulatorsmentioning
confidence: 99%